2005
DOI: 10.1074/jbc.m411914200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Human Cystatin D, a Cysteine Peptidase Inhibitor with Restricted Inhibition Profile

Abstract: Cystatins are natural inhibitors of papain-like (family C1) and legumain-related (family C13) cysteine peptidases. Cystatin D is a type 2 cystatin, a secreted inhibitor found in human saliva and tear fluid. Compared with its homologues, cystatin D presents an unusual inhibition profile with a preferential inhibition cathepsin S > cathepsin H > cathepsin L and no inhibition of cathepsin B or pig legumain. To elucidate the structural reasons for this specificity, we have crystallized recombinant human Arg 26 -cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Further structural studies of other monomeric cystatins, such as cystatin B in complex with papain (Stubbs et al, 1990), cystatin A (Martin et al, 1995;Staniforth et al, 2001) and cystatin D (Alvarez-Fernandez et al, 2005) have also been performed and suggest a common cystatin fold. This suggestion has been further corroborated on elucidation of the crystal and NMR structures of dimeric wt and L68Q cystatin C (Ekiel et al, 1997;Gerhatz et al, 1998;Janowski et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Further structural studies of other monomeric cystatins, such as cystatin B in complex with papain (Stubbs et al, 1990), cystatin A (Martin et al, 1995;Staniforth et al, 2001) and cystatin D (Alvarez-Fernandez et al, 2005) have also been performed and suggest a common cystatin fold. This suggestion has been further corroborated on elucidation of the crystal and NMR structures of dimeric wt and L68Q cystatin C (Ekiel et al, 1997;Gerhatz et al, 1998;Janowski et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…A three-dimensional model of human cystatin M/E was generated on the basis of the published crystal structure of human cystatin D (30), which revealed that the overall predicted structure of cystatin M/E closely matched that of cystatin D (Fig. 1).…”
Section: Inhibition Of Protease Activity By Cystatin M/e-based On Thementioning
confidence: 99%
“…37 Similarly, HMWK obeys a 2:1 binding stoichiometry, with different rate constants for each binding site. 38 Numerous three-dimensional structures of cystatins and stefins have been described, [39][40][41][42] whereas no structural or mechanistic data are presently available for kininogens.…”
Section: Introductionmentioning
confidence: 99%